Legal Istinbath Method and Status of Majelis Ulama Indonesia Fatwa 14/2020 During Covid-19 Pandemic - Taufik, Azhar; Supandi, Supandi; Risdianto, Risdianto (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2026)
This research aims to analyze the method of Islamic legal reasoning (istinbath al-hukm) applied by the Indonesian Ulema Council in formulating its fatwas and to examine the legal and social status of MUI‘s fatwas in Indonesian society, focusing on Fatwa No. 14 of 2020 concerning the Implementation of Worship during the COVID-19 Outbreak. The study employs a qualitative approach through library research, using primary sources such as official MUI fatwa documents, procedural guidelines, and Islamic jurisprudential references. Secondary sources include classical and contemporary fiqh literature, scholarly articles, and other relevant academic studies. The findings indicate that the MUI‘s method of istinbath is rooted in the Qur‘an and Sunnah, supported by fiqh principles (qawa‘id fiqhiyyah), classical juristic opinions, and expert consultation to ensure that the resulting fatwas serve the public interest (maslahah). Moreover, MUI‘s fatwas, while not legally binding under state law, carry strong moral and religious authority due to their basis in valid Islamic sources and their formulation through collective ijtihad. The research recommends that MUI fatwas be considered as references in the formulation of national regulations and policies, given their pivotal role in providing religious guidance and maintaining harmony among Indonesian Muslims.